2011
DOI: 10.1007/978-3-642-23160-5_6
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid and Interactive Domain-Specific Translation for Multilingual Access to Digital Libraries

Abstract: Abstract. Accurate high-coverage translation is a vital component of reliable cross language information retrieval (CLIR) systems. This is particularly true for retrieval from archives such as Digital Libraries which are often specific to certain domains. While general machine translation (MT) has been shown to be effective for CLIR tasks in laboratory information retrieval evaluation tasks, it is generally not well suited to specialized situations where domain-specific translations are required. We demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
0
1
Order By: Relevance
“…In Wu and He’s (2012) study regarding Chinese–English information retrieval, their MT systems provided high-quality translations and were more robust in handling untranslated terms; these results, however, were not consistent with other studies that reported that the language structure or the domain-specific queries contributed to weaken the MT (Jones et al , 2011; Petrelli and Clough, 2012; Ture and Lin, 2014; Vassilakaki and Garoufallou, 2013). Wu and He (2012) reported that statistical MT has increased the effectiveness of the translations: “Statistical MT has become the state of the art for MT in many application areas, and even some commercial MT systems such as Google Translate (http://translate.google.com/translate) are statistical MT systems” (p. 432).…”
Section: Literature Reviewcontrasting
confidence: 64%
“…In Wu and He’s (2012) study regarding Chinese–English information retrieval, their MT systems provided high-quality translations and were more robust in handling untranslated terms; these results, however, were not consistent with other studies that reported that the language structure or the domain-specific queries contributed to weaken the MT (Jones et al , 2011; Petrelli and Clough, 2012; Ture and Lin, 2014; Vassilakaki and Garoufallou, 2013). Wu and He (2012) reported that statistical MT has increased the effectiveness of the translations: “Statistical MT has become the state of the art for MT in many application areas, and even some commercial MT systems such as Google Translate (http://translate.google.com/translate) are statistical MT systems” (p. 432).…”
Section: Literature Reviewcontrasting
confidence: 64%